A comparison of spiritual health of male and female students in the Ilam University of Medical Sciences - Tavan, Hamed; Taghinejad, Hamid; Mousavi Moghadam, Seyyed Rahmatollah; Sayehmiri, Kouroush; Mohammadi, Iman (Archives of Advances in Biosciences, 2015)
There is a strong relationship between spiritual development of nursing students and their ability to provide patients with spiritual care. Therefore, present research aims to explore spiritual health in nursing students of theIlam University of Medical Sciences, in Iran for both boys and girls. Spiritual health of students is determined using the Palutzian andElisonquestionnaire which consisted of three parts. 10 questions were related to demographic date of students and 20 questions were examined religious health and existential health of students. Eventually, spiritual health of nursing students is classified into four groups and first group who received the grade of 20-40 has poor state of spiritual health. The groups that obtained total grades of 41-70, 71-99 and 100-120 are assigned as low-moderate, high-moderate and high status of spiritual health, respectively. Data analysis is conducted using ANOVA, Two-way analysis, and Factor analysis. The sample included 39% girls and 61% boys. Poor status of spiritual health between participants was not observed and correlation coefficient between scales of spiritual health is found to be 84.3% which represents as the score of religious health increases existential health score enhances. In order to promote spiritual health of nursing students, it is recommended that the course of spiritual health shouldbe added as a part of the curriculum for medical students due to this fact that capability of student nurses for providing spiritual care is related to their spirituality and their education in spiritual care.